Rational synthesis of polymer coated inorganic nanoparticles-MWCNT hybrids via solvophobic effects - Velasco, PQ; Karde, V; Ito, Y; Heng, JYY; Porfyrakis, K; Grobert, N (Elsevier, 2021)
The efficient synthesis of inorganic nanoparticle-carbon nanotube hybrids requires the development of models and synthetic guidelines that can be used to maximise the interactions between both nanomaterials. Herein we report the application of the Hansen surface energy based solubility parameter theory as a model for the selection of solvents that can maximise the interactions between iron oxide nanoparticles and MWCNTs. To achieve this, we synthesized iron oxide nanoparticle-MWCNT hybrid materials in three different solvents and characterized their composition with TGA. The solvent was found to have a significant impact in the final amount of iron oxide composition of the hybrids. The Hansen surface energy based solubility parameters of MWCNTs were characterized via inverse gas chromatography and were used to evaluate the interactions between the MWCNTs and the solvent media. Under this model we expected that large differences between the Hansen surface energy based solubility parameters of solvents and MWCNTs would be correlated with larger incorporation of iron oxide nanoparticles in the hybrids. The amount of iron oxide nanoparticles found in the hybrids were indeed consistent with the predictions of the Hansen surface energy based solubility parameter theory making it a powerful tool for the design of nanoparticle-carbon nanotube hybrids.